Relationship between consumer satisfaction and electronic word of mouth about restaurant experience in Sarawak, Malaysia - Tan, Chin Choo (2016)
Competition in food service industry and the introduction of social media have created a challenge in restaurant industry. This is because restaurant operators need to adapt to the new trend of electronic communication technology which may give great impact to their companies. The purpose of this study is to identify the determinant factors of customer satisfaction which may direct or indirectly affect customer return intention and involvement of electronic word of mouth (eWOM) through social media. This study is conducted in Sarawak, Malaysia where its occupants are mainly consisting of Chinese, Malay and Iban population. Convenient sampling method is utilized in collecting the samples and regression analysis is utilized to analyze the data and hypothesized both independent and dependent variables. The results of the analysis revealed that there is a significant relationship between restaurant experiences towards customer satisfaction, return intention and eWOM respectively. It is proved that eWOM is significantly related to customer satisfaction and return intention. This means that the utilization of eWOM would most likely assist the restaurant operators in their business. eWOM as the new trend of communication is the main contribution of this study because it has been proven that eWOM is related to customer satisfaction, return intention and certain customer experience. Due to that, this study gives some insights to the practitioners, academicians and policy makers to assist them in different aspects and prospective fields.